Carried forward by hope, April -December 1865 - Dye, Ginny (Dye, Ginny. Bregdan chronicles series, 2015)
"America struggles to rebuild in the aftermath of Lincoln's assassination. Promises will be broken, and everyone you have grown to love will be asked to pay a high price to make freedom for the slaves more than just a mockery. Robert fights to emerge from the darkness as Carrie risks everything to bring him back to her. Moses is offered the opportunity of a lifetime, while Rose returns to her roots with a dream that will change everything. Matthew is caught up in the worst maritime disaster in American history, while Jeremy discovers the cost of embracing his true heritage. Thomas and Abby are surprised by a future they never dreamed was possible"--Author's website.